Identification of older adults' needs as future users of autonomous shuttles: A serious game co-creation approach for inclusiveness - Cesar Casiano Flores; Fien Vanongeval; Thérèse Steenberghen (Transactions on Transport Sciences, 2023)
Automated vehicles are potential disrupters of the mobility system and are expected to address inclusive mobility issues. Yet, the transition to their full implementation in cities is expected to face numerous challenges. While companies and governments interested in their future implementation have conducted pilots to understand better their implementation in cities, there is still a limited understanding of potential users' needs. This understanding becomes even more limited when considering vulnerable groups. To address this gap, we have developed a novel Serious Game named "A shuttle for everyone". We use it as a co-creation method to engage potential users, in this case, older adults in the Noordrand-Brussels region, Belgium. This study case contributes to the co-creation and transport literature as there is scarce research focused on developing new inclusive mobility public services. Three game sessions with older adults took place. The key identified needs are related to comfort, safety, ease of use, and accessibility. Our results confirm and complete previous automated vehicle studies. We can confirm that our Serious Game as a co-creation method has facilitated anticipatory needs identification. Understanding users' needs contribute to improving design and can help to create policy recommendations that aim for an inclusive implementation of automated vehicle mobility services.